Spatiotemporal evolution and multiscenario simulation of cultivated land ecosystem services in the Dongting Lake Plain - Binggeng Xie; Simi You; Kaichun Zhou (Scientific Reports)
Abstract With the rapid development of the social economy, human dependence on and interference with cultivated land ecosystems have increased. Improving the understanding of changes in ecosystem services is conducive to avoiding and reducing the risk of ecosystem service degradation. This study evaluated seven key ecosystem services of cultivated land in the Dongting Lake Plain from 2000 to 2020, analysed their spatiotemporal evolution characteristics and correlations between ecosystem service pairs, and identified the key factors driving their changes. Finally, the PLUS model was used to predict land use changes and ecosystem service responses under the baseline scenario, farmland protection scenario, and ecological protection scenario in 2040. The results revealed that (1) from 2000 to 2020, in addition to the degradation of carbon storage services and habitat quality services, the food production, environmental purification, water conservation, soil conservation and landscape aesthetic services of the Dongting Lake Plain all showed increasing trends. The high- and low-value areas of each ecosystem service vary, but the overall spatial pattern is relatively stable. (2) In 2000, 2010 and 2020, the proportions of trade-off relationships among the 21 ecosystem service pairs in the Dongting Lake Plain were 52.38%, 51.74% and 28.57%, respectively. During the study period, the dominant correlation between ecosystem services shifted from trade-offs to synergies. (3) Ecosystem services are influenced by both natural background conditions and human activities. Natural factors have a greater impact than do socioeconomic factors. Precipitation, temperature and altitude are the key factors driving changes in ecosystem services. (4) The simulation results of multiple scenarios reveal that by 2040, the cultivated land in the Dongting Lake Plain will suffer the greatest loss under the baseline scenario, with the percentage decreasing from 54.07% to 51.64%. In addition to the improvement of environmental purification services, the total amount of various services will also increase. The reduction is the most significant in this scenario, followed by the ecological protection scenario. In the farmland protection scenario, ecosystem services are protected to a certain extent.